EVALUASI PROGRAM BEASISWA UNGGULAN PADA KEMENTERIAN PENDIDIKAN DAN KEBUDAYAAN EVALUATION OF SCHOLARSHIP PROGRAM THE MINISTRY OF EDUCATION AND CULTURE - Hawignya, Hawignya (issn 1978-6573, 1978)
Abstract This study aims to uncover the scholarship program goals, explain the nominee selection mechanism, explaining how the scholarship distribution process, explaining the process of monitoring the implementation and effectiveness of the program reveals. The research was conducted at the Bureau of Planning and International Cooperation and the University of the organizers.Research Scholarship Program evaluation using the evaluation model approach Context, Input Process, and Product (CIPP) by Daniel L. Stufflebeam. Data be collected through interviews, document study and observation.The results showed that: 1) The legal basis used is robust and has been seen to work. 2) the selection mechanism needs to be fixed. 3) The process of distribution of scholarship many obstacles aspecially in the begining of the fiscal year. 4) Monitoring the implementation of the program has not been programmed. 5) The effectiveness of the program has been much felt. The findings in this study are expected to be useful for the development of scholarship and to increase the quaity of human resource of Indonesia. Keywords: legal basis and purpose, selection Mechanism scholarship recipients, scholarship distribution process, process monitoring, and program effectiveness. Abstrak Penelitian ini bertujuan untuk menjelaskantujuan program beasiswa, mekanisme seleksi calon penerima, bagaimana proses penyaluran beasiswa, proses monitoring pelaksanaan, dan efektivitas program. Penelitian ini dilaksanakan di Biro Perencanaan dan Kerjasama Luar Negeri dan Universitas penyelenggara.  Penelitian evaluasi Program Beasiswa Unggulan ini menggunakan pendekatan model evaluasi Context, Input Process, dan Product (CIPP) oleh Daniel L. Stufflebeam. Pengumpulan data dilakukan melalui wawancara, studi dokumen, dan observasi.Hasil penelitian menunjukkan bahwa: 1) Dasar hukum yang digunakan sudah kuat dan telah tampak hasilnya. 2) Mekanisme seleksidi Biro Perencanaan dan Kerjasama Luar Negeri perlu diperbaiki. 3) Proses penyaluran beasiswa banyak mengalami kendala, terutama di awal tahun anggaran. 4) Monitoring pelaksanaan program belum terprogram karena terbatasnya anggaran. 5) Efektivitas program sudah banyak dirasakan oleh alumni.Temuan dalam penelitian ini diharapkan akan bermanfaat bagi pengembangan beasiswa unggulan dan peningkatan mutu serta daya saing sumber daya manusia Indonesia. Kata kunci: Dasar hukum dan tujuan, mekenisme seleksi calon penerima beasiswa, proses penyaluran beasiswa, proses monitoring, dan efektivitas program.